INQUIRE: A Case Study in Evaluating the Potential of Online NCQ Tests in a Discursive Subject - New, S; Clarke, S; Lindsay, K; McKenna, C (2004)
There has been a wealth of investigation into the use of online multiple-choice questions as a means of summative assessment, however the research into the use of formative MCQs by the same mode of delivery still remains patchy. Similarly, research and implementation has been largely concentrated within the Sciences and Medicine rather than the more discursive subjects within the Humanities and Social Sciences. The INQUIRE (Interactive Questions Reinforcing Education) Evaluation Project was jointly conducted by two groups at the University of Oxford-the Saïd Business School and the Academic Computing Development Team to evaluate the use of online MCQs as a mechanism to reinforce and extend student learning. This initial study used a small set of highly focused MCQ tests that were designed to complement an introductory series of first-year undergraduate management lectures. MCQ is a simple and well-established technology, and hence the emphasis was very much on situating the tests within the student experience. The paper will cover how the online MCQs are intended to fit into the Oxford Undergraduate study agenda, and how a simple evaluation was executed and planned to investigate their usage and impact. The chosen method of evaluation was to combine focus groups with automated online methods of tracking, and the paper discusses the findings of both of these.